Categorizing Taxpayers: A Mixed-Method Study on Small Business Tax Compliance in the Philippines - Angeles, Imelda T. (UI Scholars Hub, 2021)
Research Aims: The purpose of this study is to determine the underlying reasons behind the management’s tax compliance and non-compliance decisions. Design/methodology/approach: This study employed a mixed-method research approach in which the scale observations of taxpayers’ tax compliance practices and the taxpayers' lived experiences and perspectives about tax where integrated. The quantitative approach utilized binary logistic regression, and the qualitative approach used thematic and joint-result analyses. Research Findings: The integration of the two research methods revealed three distinct types of taxpayers: impulsive, reflective, and active. The result indicates that the taxpayer's compliance behavior may have an effect on the sustainability of the country's firms, implying that the taxpayer's compliance behavior may manifest in management practices and governance. Theoretical Contribution/Originality: The study's development adds to the body of knowledge of the three types of taxpayers who rationalize their tax compliance and non-compliance. These taxpayers’ characteristics are a meta-inference of the effect of tax filing experience and tax morale, and the taxpayers’ emerged attitudes substantiated by their perspective on tax. Managerial Implications in the Southeast Asian context: Tax evasion may be a symptom of a larger issue with public finance, law enforcement, organizational architecture, or an organization's ethical standards. A complying owner or management exhibits ethical ideals in their business practices. Taxpayers' ability and willingness to comply with tax regulations will afford management with more opportunities to attract more investors and partners because of ethical and good governance practices. Research limitations and implications:The mixed-method approach elucidates why taxpayers have diverse motivations for tax compliance. This study adds to the literature a new perspective on tax compliance.